2022
DOI: 10.3390/ma15062214
|View full text |Cite
|
Sign up to set email alerts
|

Impact Abrasive Wear Property of CrAlN/TiSiN Multilayer Coating at Elevated Temperatures

Abstract: The impact wear property of hard coatings at elevated temperatures is of particular interest for applications in nuclear power plants. This study evaluated the impact wear behavior of two CrAlN/TiSiN coatings with and without sand. Alternately grown CrAlN and TiSiN films with modulation periods of 455 and 19 nm were formed in a columnar structure. The nanomultilayer shows better impact wear resistance than multilayer films with and without sand. The energy absorption rate has a similar trend to wear rate, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Studies of wear-resistant coatings based on Ti-N, Zr-N, Mo-N and Cr-N coatings show their high hardness and excellent tribological characteristics. Such coatings are promising materials for wide application, for example, as protective coatings against rapid tool wear [1][2][3][4][5][6][7][8][9][10][11]. Along with this, the structure and tribological properties of W-N coatings have not been studied much.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of wear-resistant coatings based on Ti-N, Zr-N, Mo-N and Cr-N coatings show their high hardness and excellent tribological characteristics. Such coatings are promising materials for wide application, for example, as protective coatings against rapid tool wear [1][2][3][4][5][6][7][8][9][10][11]. Along with this, the structure and tribological properties of W-N coatings have not been studied much.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of scientific research is devoted to the study of the material properties of nanostructured coatings with universal [13] and high wear-resistant characteristics [3,[14][15][16]. Among various coatings, nitride nanocomposite or nanolayer systems are studied quite widely [5,7,9,11,13,14]. Transition metal nitrides are considered as a protective coating due to their excellent properties in terms of hardness, wear resistance and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Liew [ 21 ] showed that the multilayer AlCrN/TiAlN coated tool had higher delamination, abrasion and fracture resistance than the TiAlN single-layer coated tools. Recently, Y. Luo et al [ 22 ] showed that the multilayer coating of AlCrN/TiSiN with nanoscale modulation thicknesses possessed high plasticity index and impact wear resistance to abrasive quartz particles. Presently, there are only a few reports on multilayer coatings composed of TiAlNbN and AlCrN, and particularly their tribological performance has not been widely studied [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%